Elementos de uma poética jornalística do acontecimento: narrativas do massacre de Realengo em Veja e Folha de S. Paulo - Leandro Rodrigues Lage (2013)
This dissertation addresses the journalistic narratives about the massacre of Realengo as mediations of the event experience. Along the way, one faces the question of journalistic narrative within the studies in journalism, traditionally concerned with formal and discursive dimensions of this activity, seeking shelter in a theoretical horizon opened by ricoeurian narrative hermeneutics in order to enable observe these narratives in their ethical, aesthetic and poetic dimensions. From the analysis of the coverage of Veja magazine and newspaper Folha de S. Paulo about that massacre, seeks to understand the configurational dinamic of the event, what we call a poetic of journalism - an allusion to Greek poíesis, ie, the poetic work - especially with regard to the explanatory gesture intrinsic to narrative work. It examines the concept of event covering various theoretical approaches to what is the meeting point between a pragmatist philosophy and a hermeneutic perspective, that allow to overcome a constructivist approach of the event in favor of narrative comprehension without obliterating its sensitive dimension. Analyzes the narratives of Veja and Folha de S. Paulo in search of causal textures that enable understand the narrative work operated by these journalism media, reaping evidence of a poetics of journalistic work as event mediator that not only narrates the event, but also acts as a understanding vector of that experience.